Brottsligheten och fängarnas psykosociala bakgrund - Mattila, Vilho J.; Salokangas, Raimo K. R.; Jäppinen, Vilho I.; Joukamaa, Matti I.; Salmi, Lauri; Holm, Hannu (Nordisk Tidsskrift for Kriminalvidenskab, 1980)
See abstract in article.